Analyzing the Role of Myanglung Bazar in Promoting Local Agricultural Products - Teyung , Nir Bahadur (Intellectual Journal of Academic Research, 2024)
Agricultural products are pivotal for the Nepalese market, serving as a primary source of income. The market dynamics indicate a significant dominance of Indian imports over local exports. This study aims to analyze the socio-economic impact of Myanglung Bazar and its income-generating activities, focusing on its role in rural development and poverty alleviation. A descriptive cross-sectional and analytical research design was employed, targeting the agricultural product market in Myanglung Bazar. Findings indicate that effective agricultural production and promotional movements in Myanglung Bazar contribute to self-dependency in agricultural product promotion, reducing reliance on Indian imports. The study underscores the importance of local agricultural markets in fostering rural development and enhancing income generation in Nepal.